Deploying Reactive microservices : strategies and tools for delivering resilient systems - Callahan, Edward (O'Reilly Media, 2017)
Just as a high-rise tower depends on a suitably resilient, purpose-built foundation for stability, Reactive microservices need to be deployed to a Reactive-based deployment system if you're to get the most out of them. This practical report shows you how to automate the deployment, scaling, and management of Reactive applications across a distributed cluster, using deployment tooling designed for the purpose. Lightbend senior engineer Edward Callahan guides you step-by-step through the process with the Lightbend Enterprise Suite, an out-of-the-box toolkit that helps you build, manage, and monitor Reactive applications. The tools in this suite are themselves Reactive applications. This report features a series of exercises to help you deploy a sample Java-based application, hands-on, using this toolkit. You will learn: The ease with which you can scale an application's services up and down How Reactive systems provide process resilience during service interruptions Techniques for performing a rolling upgrade of an application's key services How the Lightbend Enterprise Suite enables callers to locate the correct service addresses A solution for collecting and consolidating logs generated by the application Out-of-the-box defenses against network partitions that occur when parts of the network become unreachable.